Determinants of consumers' frequency of eating out: implication for the restaurant business in India. (15th December 2021) - Khan, Waseem; Ansari, Saghir Ahmad; Siddiquei, Mohd Imran
This article has examined the determinants of consumers' frequency of eating out through primary survey conducted on 157 urban respondents, interviewed through a structured questionnaire. Of the total respondents, 41% of respondents reported eating out more than four times in a month. The estimates of Poisson count regression model (PCRM) indicate that consumers' high frequency of eating out was significantly prominent among males, young, self-employed, vegetarian, prefer Indian cuisine, spend less than 1, 000 rupees per visit and get regular advertising messages. In the end, the study also presents the implication for development of restaurant industry.